The Influence of Career Advancement, Job Promotion, and Competence on Employee Performance Through Work Motivation As An Intervening Variable: (A Study at Education Office Of Kabupaten Jember) - Syamilah, Aliyatus; Cahyono, Dwi; Sanosra, Abadi; Said, Nur (Journal of Economics and Business UBS, 2024)
This article delves into the intricate dynamics of Human Resource Management (HRM) in the Education Office of Jember Regency, with a specific focus on the interplay between career advancement, job promotion, employee competence, and employee performance. Drawing on the AMO (Ability, Motivation, Opportunity) framework, this research investigates the direct and indirect impacts of these factors through a comprehensive survey of 80 Education Office employees. The research findings reveal a significant positive influence of career advancement and job promotion on employee motivation and performance. The anticipated direct impact of employee competence on work motivation also proves to be significantly positive. These findings underscore the importance of structured career paths, promotions, and competence in shaping a motivated workforce and enhancing overall employee performance. This research contributes to bridging knowledge gaps in HRM practices and provides practical interventions for organizational improvement. The proposed insights offer a foundation for organizational leaders and HR practitioners to enhance employee motivation and performance holistically.